EVALUATION OF FERMENTED FINISHER PHASE OF BROILER CHICKENS RATE USING LIGNOCELLULOLYTIC PROBIOTIC BACTERIA - T.D.V.F, Gabrella; Mudita, I M.; Suryani, N. N. (Jurnal Peternakan Tropika, 2022)
This study aimed to evaluate the content of the finisher phase broiler ration fermented using lignocellulolytic probiotic bacteria as an effort to replace AGPs. This research was carried out at the Sesetan Laboratory and the Nutrition and Animal Feeding Laboratory, Faculty of Animal Husbandry, Udayana University from May to June 2021. The design used was a completely randomized design (CRD) with four treatments and four replications. The four treatments were broiler chicken rations without lignocellulolytic probiotic bacteria as a control (AB0), broiler chicken rations using Bacillus subtilis BR4LG bacteria as much as 5% of the total ration (AB1), broiler chicken rations using Bacillus sp . BT3CL as much as 5% of the total ration (AB2), broiler chicken rations using Bacillus sp .BT8XY bacteria inoculants as much as 5% of the total ration (AB3). The variables observed were dry matter (BK), organic matter (BO), ash, crude protein (PK), crude fiber (SK) and crude fat (LK) and gross energy (GE). The results showed that the use of lignocellulolytic probiotic bacteria in the diet gave significant differences (P<0.05) to dry matter, crude protein, crude fiber and crude fat, while the result we’re not significantly different from organic matter and ash difference (P>0.05) compared control (AB0). From the results of the study, it can be concluded that the fermented ration using lignocellulolytic probiotic bacteria can increase the nutritional content such as crude protein (21.70%) and gross energy (4.01 Kcal/g) but does not affect organic matter (90.15%) ash (10.80%). The fermented ration using lignocellulolytic probiotic bacteria was able to reduce crude fiber (2.92%) and crude fat (7.92%).   Keywords: fermentation, lignocellulolytic bacteria, finisher phase broiler chicken, nutrional content .